The Power of Emotional Branding: How Brand Awareness, Characteristics, and Self-Brand Congruity Drive Purchasing Decisions - Rizkautami, Puspa; Tuti, Meylani (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Recognising the psychological and emotive factors influencing consumer purchasing decisions is indispensable for brand success in the competitive market. This study investigates the impact of brand awareness, brand attributes, and brand congruence on purchasing decisions, with emotional branding as a mediating variable. The employed approach is quantitative. The participants in this study were coffee customers from various renowned coffee establishments in Jakarta. Utilising an accidental sample method, specifically engaging customers who coincidentally encountered the author, yielded 201 respondents. The data analysis employed the Structural Equation Model with SmartPLS. The findings indicated that brand awareness and congruence substantially affected purchasing decisions directly and via emotional branding. Brand features did not dramatically affect buying decisions, suggesting that other elements, such as consumer-brand emotional connections, significantly influenced purchasing behaviour. Furthermore, emotional branding was validated as the primary mediating variable, enhancing the correlation between brand-related characteristics and consumer decision-making. These findings underscore the significance of establishing robust emotional connections with consumers, rather than depending exclusively on brand features, to stimulate buying intentions. Brands should enhance their emotional engagement tactics to foster customer loyalty and successfully affect consumer behaviour.